2020
DOI: 10.3389/fimmu.2020.572323
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and lncRNAs—A New Layer of Myeloid-Derived Suppressor Cells Regulation

Abstract: Myeloid-derived suppressor cells (MDSCs) constitute an important component in regulating immune responses in several abnormal physiological conditions such as cancer. Recently, novel regulatory tumor MDSC biology modulating mechanisms, including differentiation, expansion and function, were defined. There is growing evidence that miRNAs and long non-coding RNAs (lncRNA) are involved in modulating transcriptional factors to become complex regulatory networks that regulate the MDSCs in the tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 156 publications
(178 reference statements)
0
20
0
Order By: Relevance
“…The development of MDSCs is a complex phenomenon consisting of increased production of IMCs in the bone marrow, inhibition of the terminal differentiation of IMCs, and pathological activation of MDSCs. Multiple factors secreted from cancer or stromal cells, such as macrophage colony-stimulating factor, granulocyte colony-stimulating factor (G-CSF), granulocyte monocyte colony-stimulating factor, vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-β), tumor necrosis factor-alpha, prostaglandin E2 (PGE2), interleukins (IL-1β, IL-10, IL-4, and IL-6), and noncoding RNAs (microRNAs and long noncoding RNAs) are involved in these processes [ 4 , 8 , 10 ]. In addition to these, recent investigations have suggested that tumor-derived exosomes are involved in the development of MDSCs through the communication with bone marrow cells [ 11 ].…”
Section: Mdsc Development Activation and Recruitmentmentioning
confidence: 99%
“…The development of MDSCs is a complex phenomenon consisting of increased production of IMCs in the bone marrow, inhibition of the terminal differentiation of IMCs, and pathological activation of MDSCs. Multiple factors secreted from cancer or stromal cells, such as macrophage colony-stimulating factor, granulocyte colony-stimulating factor (G-CSF), granulocyte monocyte colony-stimulating factor, vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-β), tumor necrosis factor-alpha, prostaglandin E2 (PGE2), interleukins (IL-1β, IL-10, IL-4, and IL-6), and noncoding RNAs (microRNAs and long noncoding RNAs) are involved in these processes [ 4 , 8 , 10 ]. In addition to these, recent investigations have suggested that tumor-derived exosomes are involved in the development of MDSCs through the communication with bone marrow cells [ 11 ].…”
Section: Mdsc Development Activation and Recruitmentmentioning
confidence: 99%
“…However, the complex microenvironment of tumors can mediate immune escape, leading to the failure of immunotherapy [56]. lncRNAs are overexpressed during the development, differentiation and activation of immune cells, such as macrophages, dendritic cells, neutrophils, T cells, B cells and bone marrow mesenchymal stem cells [57]. Recent studies have found that lncRNAs are involved in various processes of the immune response in the TME and the promotion of tumor immunosuppression [58] and play a role in the evaluation and measurement of the immunotherapeutic response in various cancers, such as endometrial cancer and liver cancer [59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the number of miRs contributing to MDSCs function is increasing and has been reviewed in detail elsewhere. 107…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%